Foetal growth and duration of gestation relative to water chlorination. Issue 7 (1st July 2001) - Jaakkola, J J K; Magnus, P; Skrondal, A; Hwang, B-F; Becher, G; Dybing, E
Abstract : OBJECTIVE: To assess the effect of exposure to chlorination byproducts during pregnancy on foetal growth and duration of pregnancy. METHODS: A population based study was conducted of 137 145 Norwegian children born alive in 1993–5. Information was obtained from the Norwegian medical birth registry, waterwork registry, and social science data service. The outcomes of interest were birth weight, low birth weight (<2500 g), small for gestational age, and preterm delivery (gestational age <37 weeks). The exposure assessment was based on quality of drinking water in the municipality where the mother lived during pregnancy. Municipal exposure was calculated with information on chlorination and the amount of natural organic matter in raw water measured as colour in mg precipitate/l. The main exposure category was high colour and chlorination, which was contrasted with the reference category of low colour and no chlorination. RESULTS: In logistic regression analysis adjusting for confounding, the risks of low birth weight (odds ratio (OR) 0.97, 95% confidence interval (95% CI) 0.89 to 1.06) and small for gestational age (OR 1.00, 95% CI 0.91 to 1.10) were not related to exposure. Contrary to the hypothesis, the risk of preterm delivery was slightly lower among the exposed than the reference category (OR 0.91, 95% CI 0.84 to 0.99). The risks of the studied outcomes were similar in newborn infants exposed to high colour drinking water without chlorination and chlorinated drinking water with low colour compared with the reference category. CONCLUSIONS: The present study did not provide evidence that prenatal exposure to chlorination byproducts at the relatively low concentrations encountered in Norwegian drinking water increases the risk of the studied outcomes.